Mitigating Online Risk Through Trust: A TPB Approach - Dudi Permana; Hasbin; C. Catur Widayati; Hasliza Abdul Halim (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
In the growing digital economy, online shopping presents inherent risks, especially post-pandemic, making consumer trust a critical factor. The Theory of Planned Behavior (TPB) offers a framework for understanding these dynamics and their impact on consumer behaviour. This study explores how trust mitigates perceived online shopping risks, influencing consumer purchase decisions and intentions. The study uses a quantitative approach, surveying 251 consumers who engaged in online shopping during the pandemic and employing TPB to assess trust's mediating role in reducing perceived risks. The study reveals that financial, product, and security risks negatively affect online purchase intention, while trust significantly mediates these effects, enhancing consumer confidence in digital platforms. E-commerce platforms should build trust by improving security, product quality, transparency, and customer service to reduce perceived risks and drive purchase intention. This study integrates multiple risk dimensions within the TPB framework and highlights trust as a pivotal mediator, particularly in the post-pandemic era.